POLICY STRATEGY FOR MAKING CHILD IDENTITY CARDS (KIA) AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF MAKASSAR CITY - Fajrin, Muhammad; Sakawati, Herlina; Aina, Asri Nur (Jurnal Aktor, 2025)
This research aims to determine the Policy Strategy for Making Child Identity Cards at the Makassar City Population and Civil Registration Office. Descriptive research type with a qualitative approach. Data collection techniques through observation, interviews and documentation. The data analysis technique uses the Miles, Huberman and Saldana model, namely data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the Policy Strategy for Making Child Identity Cards at the Makassar City Population and Civil Registration Office is based on Geoff Mulgan's (2009) public strategy indicators, namely: Purposes, Environment, Direction, Action, and Learning, that in general the policy strategy is still not optimal, it is hoped that the Purpose indicator can be realised its usefulness value and the Environment and Direction can be maximised. Supporting factors 1). Schools that help collect student data and collect student data. 2). Collaboration carried out by the government with companies or shops that have helped through promos. 3). Free KIA making so that it supports all levels of society. Inhibiting factors 1). The mindset and awareness of the community to comply with policies is still lacking and does not understand what the uses and benefits of KIA are. 2). There are no sanctions for people who do not have KIA, either in the form of administrative sanctions or other sanctions. 3). Limited in terms of budget, human resources, and inadequate infrastructure